2016
DOI: 10.1007/s00467-016-3429-y
|View full text |Cite
|
Sign up to set email alerts
|

Beginning the trajectory to ESKD in adult life: albuminuria in Australian aboriginal children and adolescents

Abstract: Compared with non-Aboriginal children, Aboriginal children are of higher risk of albuminuria when overweight or obese. We hypothesise that overweight and obesity are key contributors to the development of adult onset CKD among Aboriginal Australians, which needs further exploration in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Likewise, there are reports on the prevalence of albuminuria (8.3% vs. 2.1%) in newborn infants with low birth weights when compared to normal-weight newborns [ 67 ]. Some studies also report a similar albuminuria prevalence in ethnic groups [ 66 ], even when others show differences in albuminuria levels in Australian aboriginal and non-aboriginal people [ 68 ]. It is important to emphasize that in the latter study, the difference observed in Australian aboriginal people is associated with obesity, which was already discussed previously.…”
Section: Resultsmentioning
confidence: 98%
“…Likewise, there are reports on the prevalence of albuminuria (8.3% vs. 2.1%) in newborn infants with low birth weights when compared to normal-weight newborns [ 67 ]. Some studies also report a similar albuminuria prevalence in ethnic groups [ 66 ], even when others show differences in albuminuria levels in Australian aboriginal and non-aboriginal people [ 68 ]. It is important to emphasize that in the latter study, the difference observed in Australian aboriginal people is associated with obesity, which was already discussed previously.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, an Australian cross-sectional study with a sample of 975 children also reported a negative correlation between albuminuria and overweight or obesity [ 22 ]. Moreover, a prospective cohort study by Kim et al, involving 3418 children, discovered that the risk of albuminuria in children decreased as the BMI standard deviation score increased [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective population-based cohort study in New South Wales -The Antecedents of Renal Disease in Aboriginal Children (ARDAC) Study, initiated in 2002, aimed to determine whether Aboriginal children have an increased risk of albuminuria in childhood, the ultimate goal being to identify factors that can reduce the incidence of Aboriginal CKD [7]. This large study did not show race to be associated with albuminuria, compared to female gender and lower birth weight which were found to associated with an increased risk of persistent albuminuria.…”
Section: Australia-aboriginal and Torres Strait Islandersmentioning
confidence: 99%